Young transgender individuals' lived experiences of facing life's challenges: a qualitative study in Iran - Mohammadi, Fateme; Masoumi, Seyedeh Zahra; Tehranineshat, Banafsheh; Oshvandi, Khodayar; Bijani, Mostafa (Frontiers in Public Health, 2023)
Introduction: In recent years, several studies have addressed the challenges and psychological issues that transgender individuals face; however, only a few studies have explored the experiences of this population in Iran. Life experiences are heavily influenced by the dominant religious and cultural conditions as well as common beliefs in a society. The present study aims to investigate the transgender individuals, perception of facing life’s challenges in Iran. Methods: This study is a qualitative study with a descriptive, phenomenological design. Data were collected using semi-structured, in-depth interviews with 21 transgender individuals. The collected data were analyzed according to Colaizzi's method. Results: Analysis of the qualitative data resulted in the emergence of three themes and 11 subthemes. The three main themes included mental health disparities (fear of having one’s secret revealed , depression and despair, suicidal thoughts, secrecy in the family), gender dysphoria (contradictory gender identity, contradictory behaviors), and stigma as well as insecurity (sexual abuse, social discrimination, disrupted occupational performance, lack of support, disrepute and disgrace). Conclusions: The findings of the study suggest that transsexuals in Iran are exposed to considerable mental health disparities. In addition to disrepute, infamy, and stigma, transsexuals are faced with sexual abuse, social discrimination as well as lack of family social support. The results of the present study can help mental health experts and the healthcare system as a whole adjust their mental and physical health programs according to the needs and experiences of transsexuals along with their families. It is suggested that future research address the problems and psychological challenges transsexuals’ families have to confront.